2021
DOI: 10.3390/qubs5040033
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Neutron Dose Equivalent within and Outside of a LINAC Treatment Vault Using a Neutron Survey Meter

Abstract: This work concerns neutron doses associated with the use of a Siemens Primus M5497 electron accelerator, which is operated in the photon mode at 15 MV. The conditions offer a situation within which a fraction of the bremsstrahlung emission energies exceed the photoneutron threshold. For different field sizes, an investigation has been made of neutron dose equivalent values at various measurement locations, including: (i) At the treatment table, at a source-surface distance of 100 cm; (ii) at the level of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Duong et al investigated neutron dose rate for different field sizes at various locations within and outside of a 15 MV Siemens Primus M5497 electron accelerator treatment vault using a neutron survey meter. This study showed that low values ranging from unobservable to between 0.0001 to 0.0002 mSv/h neutron dose rate around the control room and patient waiting area where the greatest value at the level of the floor directly adjacent to the treatment couch is 8.6 mSv/h which exceeds the greatest value on the treatment table 5.5 mSv/h [14]. In the present study, we have measured neutron dose rate for 15 MV photon beam at various locations inside the Linac treatment room as a function of delivered photon dose, field size(s) and at various location inside the treatment room.…”
Section: Introductionmentioning
confidence: 77%
“…Duong et al investigated neutron dose rate for different field sizes at various locations within and outside of a 15 MV Siemens Primus M5497 electron accelerator treatment vault using a neutron survey meter. This study showed that low values ranging from unobservable to between 0.0001 to 0.0002 mSv/h neutron dose rate around the control room and patient waiting area where the greatest value at the level of the floor directly adjacent to the treatment couch is 8.6 mSv/h which exceeds the greatest value on the treatment table 5.5 mSv/h [14]. In the present study, we have measured neutron dose rate for 15 MV photon beam at various locations inside the Linac treatment room as a function of delivered photon dose, field size(s) and at various location inside the treatment room.…”
Section: Introductionmentioning
confidence: 77%
“…The calculation results of the neutron flux on the surface of the water phantom at a voltage of 15 MV, 18 and 25 MV are, respectively, 1.82  10 11 n/cm 2 .s, 2.12  10 11 n/cm 2 .s, and 4.94  10 11 n/ cm 2 .s. Neutron flux impinging on the phantom can cause an increase in the total dose, which is the sum of the photon dose and the neutron dose [19,20,21] . The addition of a neutron dose is formed through a fast neutron scattering mechanism with hydrogen atoms [22] .…”
Section: Visualization and Calculation Of Contaminant Neutron Fluxmentioning
confidence: 99%
“…In previous studies, the measurement of photoneutrons was more often carried out free-in-air at various locations in the patient plane [9,[11][12][13] or in the water phantom [11,14]. Various types of equipment can be used for measurement, including a Bonner sphere spectrometer [15], a nested neutron spectrometer (NNS, Detec Inc., Gatineau, QC, Canada) [16], a Meridian Neutron Survey Meter 5085 (HPI, Goleta, CA, USA) [12], and CR-39 detectors [14].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the measurement of photoneutrons was more often carried out free-in-air at various locations in the patient plane [9,[11][12][13] or in the water phantom [11,14]. Various types of equipment can be used for measurement, including a Bonner sphere spectrometer [15], a nested neutron spectrometer (NNS, Detec Inc., Gatineau, QC, Canada) [16], a Meridian Neutron Survey Meter 5085 (HPI, Goleta, CA, USA) [12], and CR-39 detectors [14]. Photoneutron dosimetry is a challenge because the measurement is carried out in a mixed field with photons, which can lead to an uncertainty of about 10% due to the saturation of the detector and the strong dependence of the detector response on the neutron spectrum [17].…”
Section: Introductionmentioning
confidence: 99%